Imaginary communities : utopia, the nation, and the spatial histories of modernity - Wegner, Phillip E., 1964- (University of California Press, 2002)
Drawing from literary history, social theory, and political critique, this far-reaching study explores the utopian narrative as a medium for understanding the social space of the modern nation-state. Considering the narrative utopia from its earliest manifestation in Thomas More's sixteenth-century work Utopia to some of the most influential utopias of the late nineteenth and twentieth centuries, this book is an astute study of a literary genre as well as a nuanced dialectical meditation on the history of utopian thinking as a quintessential history of modernity. As he unrave.